THE PREVALENCE OF IDENTITY CRISIS AMONG YOUTHS AND SOCIAL WORKER INTERVENTION IN IKENNE LGA OF OGUN STATE - Agbon Azorondu, Abigail; Ikechukwu Emejuru , PhD Peter; Francis Uwagbale, Raymond; Ocheze Happiness, Adesanya (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
Identity crisis has become a global concern in recent years. Several authors have researched around the subject in the field of psychology, social works and public health. Currently, several studies are being conducted to discover new methods to handle the issue of identity crisis especially among youths in secondary schools. As a result, this paper appraises prevalence of identity crisis among youths in Ikenne Local Government Area of Ogun State, Nigeria. The paper adopted correlational survey design to appraise the pattern of relationship between self-efficacy, parental supports, peer influence, internet usage and sense of identity among youths. The paper studied two hundred and sixty youths (121 Males and 139 Females) between 15-25 years (x = 13.05 and SD = 14.2) were drawn from youths in Ikenne LGA using simple random sampling technique in four stages. Results showed that youth sense of identity has negative relationship with self-efficacy (r = -.441 and p<.05) and positive relationship with peer influence (r = .253 and p<.05). The was no significant relationship with parental supports and internet usage on identity crisis. Multiple regression analysis showed that independent variables contributed 21% of the variance in youth’s identity crisis. Self-efficacy was most potent (? = -409; t (258) = .6963; p<0.05) contributing in predicting identity crisis. The paper concluded that identity crisis is mostly prevalent among the youths in Ikenne due to parental neglect as a result of busy schedule at work. Also, social workers are suitable intermediaries between youths who have lost their identity and their self-discovery. The paper recommends that secondary school administration in Ikenne LGA should make efforts toward educating their students in aspect managing frustration and lack of concentration which are identified behaviours that affect the youths. Social workers should educate parents and caregivers on the causes and effects of identity crisis in other to help reduce the rate of occurrence among the youths.